2017
DOI: 10.4103/jnrp.jnrp_445_16
|View full text |Cite
|
Sign up to set email alerts
|

Mean Platelet Volume and Platelet Distribution Width Level in Patients with Panic Disorder

Abstract: Background:Changes in platelet indices have been reported in patients with panic disorder (PD). However, previous study findings are contradictory and inconclusive. The aim of this study was to evaluate and compare the platelet indices in patients with PD.Materials and Methods:Patients with PD (n = 123) and healthy controls (n = 133) were enrolled in this case control study. The platelet indices (mean platelet volume [MPV] and platelet distribution width [PDW]) along with red blood cell (RBC) indices (RBC coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
30
2
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 40 publications
3
30
2
6
Order By: Relevance
“…The present study found a decreased trend of RBC levels in patients with PD, statistically not significant, which is probably due to increased oxidative stress and could be justified by increased RDW in these patients, as elevated RDW has been reported in depression patients (Asoglu et al, ; Bhad, ; Ransing, Patil, & Grigo, ). On the other hand, these findings were accompanied with a significant decrease in MCHC, compatible with other studies, which suggests inflammation in patients with PD, as a possible cause of elevated RDW and PDW (Huang & Hu, ; McClung & Karl, ; Vogelzangs, Beekman, de Jonge, & Penninx, ).…”
Section: Discussioncontrasting
confidence: 53%
“…The present study found a decreased trend of RBC levels in patients with PD, statistically not significant, which is probably due to increased oxidative stress and could be justified by increased RDW in these patients, as elevated RDW has been reported in depression patients (Asoglu et al, ; Bhad, ; Ransing, Patil, & Grigo, ). On the other hand, these findings were accompanied with a significant decrease in MCHC, compatible with other studies, which suggests inflammation in patients with PD, as a possible cause of elevated RDW and PDW (Huang & Hu, ; McClung & Karl, ; Vogelzangs, Beekman, de Jonge, & Penninx, ).…”
Section: Discussioncontrasting
confidence: 53%
“…Results of the studies about MPV values in panic disorder patients were contradictory. Some reported that MPV values were higher in panic disorder patients [15,16] whereas others reported otherwise [14,17]. Increased MPV was attributed to activation of platelets via α-2 receptors and decreased MPV was attributed to 5-HT transporter rate and its metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Increased MPV levels are thought to be closely related to cardiovascular disorders [13]. MPV values were studied in also schizophrenia, bipolar disorder and panic disorder with contradictory and inconclusive results [14][15][16][17][18]. We could not find any study evaluating the MPV levels in GAD patients in the literature.…”
Section: Introductionmentioning
confidence: 96%
“…[2] This issue of Journal of Neuroscience in Rural Practice includes a paper titled "Mean Platelet Volume and Platelet Distribution Width Level in Patients with Panic Disorder." [3] In this paper, authors have investigated the relationship between platelets reactivity indicators such as mean platelet volume (MPV), platelet distribution width (PDW), and platelet count; red blood cell (RBC) indices like red cell distribution width (RDW) and RBC count and Panic disorder. The study found increased PDW and RDW in patients with panic disorder compared to healthy controls.…”
mentioning
confidence: 99%